Feasibility of Material and Media Aspects in the Development of Read Rangers Application as Reading Teaching Media for Deaf Children - Maghribi, Iftitah Ulfiana; Rohmah, Anindi Nur; Saputra, Yudha Wahyu; Wulandari, Yosi (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This research aims to develop a game-based learning application called Read Rangers, specifically to test the feasibility of the media and material aspects of the application. This application is implemented in helping deaf children's reading skills in class 5 of the Deaf Department of SLBN 1 Bantul, Yogyakarta. This study used a research and development approach adapted from Borg & Gall. The research stages began with (1) an initial study to explore the existing conditions of reading learning and the relevance of using technology in the context of inclusive education. (2) Application development based on the findings from the initial study, including the integration of Javanese traditional games and augmented reality technology to facilitate interactive learning. (3) Field testing of the app, involving evaluation by material experts, media experts, as well as individual testing by deaf children. (4) Revision of the app based on feedback from the field test to improve the quality and effectiveness of learning. The results showed that the Read Rangers app obtained valiation with a decent category and very good predicate from material and media experts, as well as positive responses from field testing. This application is considered very feasible and valid to be used to improve the reading skills of deaf children in accordance with the curriculum and learning outcomes set. The implication of this research is the potential of similar applications in supporting the education of deaf children.